A responsabilidade socioambiental e a sustentabilidade corporativa: estudo de caso da celtins - Oliveira, Rita de Cassia Alves (Universidade Federal do Tocantins, 2015)
The purpose of this study is to understand the importance and effects of adopting the principles and practices of social and environmental responsibility to achieve Corporate Social Responsibility (CSR) in the companies, taking as empirical object a public utility company of electrical energy - Companhia de Energia Elétrica do Estado do Tocantins (Celtins). This purposed theme is the goal of increasing discussion in business world where you may figure out an incursion of social and environmental actions lined with institutional goals of corporations, cause the obligation to minimize or to compensate the impacts on the people and on the environment has been charged by the whole society. In this perspective, we´ve wanted to infer about these practices implications even to the sustainability of the business, or in other words, questioning how CSR is incorporated into the companies´ management process as a way to provide even the sustainability of the companies. This theoretical and empirical research has been done as a case study, following an interdisciplinary perspective, in what some aspects of Administration, Accounting, Law and Environmental Management, among others, has been addressed. From a bibliographic survey, followed by a documental analyses, in which we observed qualitative and quantitative elements concerning to economic, social, sectorial and environmental dimensions, shown in the “Relatório de Responsabilidade Socioambiental” and in the “Balanço Social” of Celtins, related to the years 2009 and 2010; even in other documents, publications, relevant law and websites of organizations related to this theme. After then, we performed structured interviews with the managers responsible for the social and environmental areas in the studied company, as a way to deepen and to correlate the studied problem through reflexive and integrative analyses of collected data, observing its repercussion on business process. We´ve realized that the convergence of corporate strategies to the social and environmental theme brings implications in both the internal and external fields, ending in confirming the theoretical presuppositions about factors that influence the strategic posture of promoting the social and environmental values, namely the searching for minimize costs and expenses in operations of corporative activities, the sectorial imperatives that command normative agenda in place, motivational factors concerned to internal working environment, related to the need to reach the company´s conception and credibility in the market. In this sense, Adopting CSR in a company can affect its management in a positive way, generating opportunities to optimize economic results, as to avoid losses as to obtain gains, while it also provides increasing reputational value in public utility concession, contributing even to the sustainability of the business.